Influence E-Commerce Transactions, Capital, and Length of Business towards The Increase Income Micro, Small and Medium Enterprises - Usman, Usman; Supriyati, Diana (Research of Economics and Business, 2023)
This study aims to determine the effect of transactions E-commerce, capital, length of business on increasing the income of micro, small and medium enterprises (UMKM in the Bekasi City area). The quantitative methodology used in this study used SPSS version 24 software to analyze data using multiple linear regression methods. A total of 274,143 research populations are MSMEs domiciled in Bekasi City. A sample of 100 respondents was calculated using the Slovin formula. Respondents were given a questionnaire to fill out, and data was collected using a Likert scale. The results showed that the effect of E-commerce transactions had an effect on increasing MSME income, capital and length of business had no effect on increasing MSME income. The Bekasi City Government needs very serious attention to the growth and development of MSME actors, especially in managing capital for MSME actors in Bekasi City so that they are able to manage capital properly and correctly so as not to go bankrupt/bankrupt, namely by providing an explanation of personal capital with appropriate business capital.